Pre-pregnancy body surface area and risk for gestational diabetes - Holopainen, Lotta; Tähtinen, Hanna (My University, 2022)
Aims To evaluate the effect of the pre-pregnancy body surface area (BSA) on the risk of gestational diabetes mellitus (GDM). Methods The study population consisted of all primiparous women with singleton pregnancies (n = 328,892) without previously diagnosed diabetes or chronic hypertension in Finland between 2006 and 2019. The information on GDM, oral glucose tolerance test (OGTT) results, and maternal backgrounds were derived from the Finnish Medical Birth Register. The pre-pregnancy BSA was calculated by using the Mosteller formula. Logistic regression models were used to estimate the association between BSA and GDM/ OGTT separately by the body mass index groups. Results A lower BSA predicted an increased risk for GDM and OGTT among the underweight (b = -2.69, SE = 0.25, p < 0.001; b = -2.66, SE = 0.23, p < 0.001, respectively) pregnant women, and normal weight (b = -0.30, SE = 0.10, p = 0.002; b = -0.67, SE = 0.09, p < 0.001, respectively) pregnant women; and pathological OGTT among the overweight (b = -0.31, SE = 0.10, p = 0.001) pregnant women. Within the obese class II or greater, a higher BSA predicted a higher risk for GDM (b = 0.74, SE = 0.12, p < 0.001) and pathological OGTT (b = 0.79, SE = 0.13, p < 0.001). Maternal smoking predicted a significantly higher risk of GDM and pathological OGTTs in almost all body mass index groups. Conclusion This study showed that in comparison to women with a higher BSA, underweight and normal weight pregnant women with a smaller BSA may be more susceptible to GDM and have a pathological OGTT.

Tutkimusaineisto koostui suomalaisista ensisynnyttäjistä ja yksöisraskauksista (n=328 892) vuosilta 2006–2019. Poissulkukriteereinä olivat aikaisempi diabetesdiagnoosi ja krooninen hypertensio. THL:n syntymärekisteritiedoista saatiin tiedot äidin taustatiedoista, tupakoinnista, sokerirasituskokeesta (OGTT) ja GDM-diagnoosikoodeista. BSA ennen raskautta laskettiin Mostellerin kaavalla käyttämällä äidin raskautta edeltävää painoa ja pituutta. Logististen regressiomallien avulla arvioitiin BSA:n sekä GDM:n ja OGTT:n yhteyttä erikseen BMI-luokittain. TULOKSET Matalampi BSA ennusti lisääntynyttä riskiä GDM:lle ja OGTT:lle alipainoisilla (b = -2.69, SE = 0.25, p < 0.001; b = -2.66, SE = 0.23, p < 0.001) ja normaalipainoisilla (b = -0.30, SE = 0.10, p = 0.002; b = -0.67, SE = 0.09, p < 0.001) raskaana olevilla naisilla; ja patologinen OGTT ylipainoisilla (b = - 0.31, SE = 0.10, p = 0.001) raskaana olevilla naisilla. Lihavuusluokassa II tai sitä ylipainoisemmissa, korkeampi BSA ennusti suurempaa riskiä GDM:lle (b = 0.74, SE = 0.12, p < 0.001) ja patologiselle OGTT:lle (b = 0.79, SE = 0.13, p < 0.001). Äidin tupakointi ennusti merkittävästi korkeampaa GDM:n ja patologisen OGTT:n riskiä lähes kaikissa painoindeksiryhmissä. PÄÄTELMÄT Tutkimus osoitti, että ali- ja normaalipainoisilla raskaana olevilla naisilla, joilla oli pienempi kehon pinta-ala (BSA), oli suurentunut riski saada GDM-diagnoosi ja patologinen OGTT tulos, verrattuna naisiin, joilla oli suhteessa suurempi kehon BSA.
Keywords: Raskausajan diabetes, kehon pinta-ala, kehon koko, tupakointi, raskaus